Efektivitas Asset Recovery dalam Tindak Pidana Korupsi - Cut Nurita (JUNCTO: Jurnal Ilmiah Hukum, 2026)
Corruption is an extraordinary crime that causes substantial losses to state finances and hinders national development. Efforts to eradicate corruption should not merely focus on punishing perpetrators but must also prioritize restoring state financial losses through an asset recovery mechanism. This study aims to analyze the effectiveness of asset recovery in restoring state losses resulting from corruption crimes in Indonesia and to identify the obstacles affecting its implementation. This research employs a normative legal research method using statutory and conceptual approaches. Data were collected through library research consisting of primary, secondary, and tertiary legal materials. The findings indicate that Indonesia has established several legal instruments supporting asset recovery, including the Anti-Corruption Law, the Law on the Prevention and Eradication of Money Laundering, and the ratification of the United Nations Convention Against Corruption (UNCAC). However, its implementation remains ineffective due to several challenges, such as difficulties in asset tracing, weak coordination among law enforcement agencies, limited human resources, complexities in legal proof, and obstacles in international cooperation. Therefore, strengthening legal regulations, enhancing the capacity of law enforcement officers, optimizing international cooperation, and accelerating the enactment of asset forfeiture legislation are necessary to improve the recovery of state losses resulting from corruption crimes.